In vitro and in vivo identification of tetradentated polyamine complexes as highly efficient metallodrugs against Trypanosoma cruzi - Olmo, Francisco; Cussó, Olaf; Marín, Clotilde; Urbanová, Kristína; Krauth-Siegel, Renate; Costas, Miquel; Ribas, Xavi; Sánchez-Moreno, Manuel (Experimental parasitology, 2016)
In order to identify new compounds to treat Chagas disease during the acute phase with higher activity and lower toxicity than the reference drug benznidazole (Bz), a series of tetraamine-based compounds was prepared and their trypanocidal effects against Trypanosoma cruzi were evaluated by light microscopy through the determination of IC50 values. Cytotoxicity was determined by flow cytometry assays against Vero cells. In vivo assays were performed in BALB/c mice, in which the parasitemia levels were quantified by fresh blood examination; the assignment of a cure was determined by PCR and reactivation of blood parasitemia levels after immunosuppression. The mechanism of action was elucidated at metabolic and ultra-structural levels by 1H NMR and TEM studies. Finally, as tetraamines are potentially capable of casuing oxidative damage in the parasites, the study was completed by assessing their activity as potential iron superoxide dismutase (Fe-SOD) and trypanothione reductase (TR) inhibitors. High-selectivity indexes observed in vitro were the basis of promoting three of the tested compounds to in vivo assays. The tests on the murine model for the acute phase of Chagas disease showed better parasitemia inhibition values than those found for Bz. Tetraamines 2 and 3 induced a remarkable decrease in the reactivation of parasitemia after immunosuppression and curative rates of 33 and 50%, respectively. Tetraamine 3 turned out to be a great inhibitor of Fe-SOD and TR. The high anti-parasitic activity and low toxicity render these tetraamines appropriate molecules for the development of an affordable anti-Chagas agent.
Gesehen am 07.07.2020